Wound coverage considerations for defects of the lower third of the leg - Babu Bajantri; R. Ravindra Bharathi; S. Raja Sabapathy (Indian Journal of Plastic Surgery)
Anatomical features of the lower third of the leg like subcutaneous bone surrounded by tendons with no muscles, vessels in isolated compartments with little intercommunication between them make the coverage of the wounds in the region a challenging problem. Free flaps continue to be the gold standard for the coverage of lower third leg wounds because of their ability to cover large defects with high success rates and feasibility of using it in acute situations by choosing distant recipient vessels. Reverse flow flaps are more useful for the coverage of the ankle and foot defects than lower third leg defects. The perforators in the lower third leg on which these flaps are based are often damaged during the injury. In medium-sized defects of less than 50 cm2 size, local transposition flaps, perforator flaps, or propeller flaps can be used. Preoperative identification by the Doppler is essential before embarking on these flaps. Of the muscle flaps, the peroneus brevis flap can be used in selected cases with small defects. In spite of all recent developments, cross-leg flaps continue to remain as a useful technique. In rare occasions when other flaps are not possible or when other options fail it can be a life boat. In the author′s practice free flaps continue to be the first choice for coverage of wounds in the lower third leg with gracilis muscle flap for small and medium defects, latissimus dorsi muscle flap for large defects and anterolateral thigh flap when a skin flap is preferred.